First-Principles Calculations of Crystallographic and Electronic Structural Properties of Au-Cu Alloys - Trong, Dung Nguyen; Long, Van Cao; Saraç, Umut; Quoc, Van Duong; Talu, Stefan; Saraç, Umut (Mdpi, 2022)
In this research, we have explored the effect of Au:Cu ratio on the crystallographic and electronic structural properties, formation energies, and radial distribution function (RDF) of Au-Cu alloy materials via density functional calculations. The results show that Au-Cu alloy can be formed in any Au:Cu ratio from 3:1 to 1:3 with a similar possibility. The results also reveal that the lattice constants of both Au and Cu are affected by the LDA-PWC pseudo-field, which is in full agreement with the experimental findings. An increase in the concentration of Cu impurity in Au results in a decrement not only in the lattice constants of the crystal system but also in the total energy of the system (E-tot). However, an enhancement in the electron density is determined by increasing Cu impurity concentration in Au. The RDF results confirm the contraction of lattice constants and a structural change in Au-Cu from cubic to tetrahedral is found when the Au:Cu ratio is equal to 1:1. These findings revealed in this work are expected to contribute to future studies on electronic materials.
Keywords: Au-Cu; Dft; Electronic Structures; Formation Energies; Lattice System